Análise das áreas verdes do município de Pato Branco - PR, e suas relações com as alterações urbanísticas e ambientais - Kunen, Adriana (2018)
The process of urbanization always leads to ambiental impacts, whether it be due to the proximity of rivers in which the cities usually begin their development, or due to deforestation, to expand their growth, said processes worsen ambiental problems even more. The green area in the urban ground plays the role of atmospheric filter and soil, groundwater and bodies of water preservation, providing the sustainability of natural resources. In general, vegetation contributes to the thermal comfort in urban areas thanks to the reduction of temperature through shading (direct effect) and evapotranspiration (indirect effect). Vegetation reduces air temperature through direct shading of the surfaces (causing less isolation absorbtion on the subjacent soil) and the conversion of sensible heat (solar radiation) into latent heat through evapotranspiration. This study has as objective to diagnose the presence of urban green areas in the municipality of Pato Branco - PR, taking into consideration aspects of urban, ambiental and legal nature during the years of 1953 to 2016. To do so, a study about the green areas of the municipality was done with the use of aerial photography mosaics (1953, 1963, 1980 and 1996) and satellite images from QuickBird (2005), Ikonos (2009) and Pleiades (2016).The use of data set and multitemporal analysis made it possible to map the urban perimeter, urban mesh and vegetal coverage of the municipality, generating informations that can subsidize the planning. The reseach results indicate that the green area in the consolidated urban perimeter grew 154% between the years of 1953-1963. And, between 1963-1980, vegetation showed a reduction of 9,6%. The biggest increment of vegetative coverage ocurred between 1980-1996, being of 3,69%. Between 1996-2016, it was identified the biggest reduction in green area coverage (36,26%). Using as reference the 2016’s urban perimiter and utilizing map algebra, and, more especifically, the tool Raster Calculater, it was possible to identify that in the year 1980, vegetation was 20,06%, rising to 26,7% in 2005 and decreasing to 24,33% in 2016. Therefore, it’s established that the Vegetal Coverage Index (VCI) from the municipality was below the recomended percebtage (30%) in all of the analyzed years. The bardships faced to the advance of vegetal coverage of Pato Branco’s municipality and, consequently, of the VCI’s between 1980 and 2016 can be explained through the elevated populational growth of the Municipality (31.470 habitants in 1980 and 75.720 habitants in 2016), the equivalent to 240%.